Combined Cr and Mo Poisoning of (La,Sr)(Co,Fe)O3-δ Solid Oxide Fuel Cell Cathodes at the Nanoscale - Skinner,SJ; Ni,N (Solid State Ionics, 2016)
Cr poisoning has been identified as a critical issue for solid oxide fuel cell (SOFC) cathodes degradation when metallic alloys are used for intermediate temperature SOFCs. In addition, Mo is also a common alloying element in ferritic stainless steel or Ni based alloys considered as interconnect materials and molybdenum trioxide is very volatile, raising concerns on Mo poisoning to the cathodes. In this work, the intrinsic reactivity of Cr with a porous (La0.6Sr0.4)0.95(Co0.2Fe0.8)O3 − δ cathode (LSCF6428) with and without the presence of Mo was investigated by transmission electron microscopy (TEM) in order to reveal the nanoscale incorporation and evolution behavior of Cr and/or Mo in LSCF. Cr incorporation was identified with formation of Cr containing phases including chromium oxide and SrCrOx with sizes of as small as ~ 100 nm, suggesting that the poisoning can take effect with subtle changes at the very small scale. Co-poisoning of Mo with Cr significantly changes the pattern of Cr behavior. CrCo2Fe3Ox spinel becomes the main reaction product in addition to chromium oxide as a result of Sr reacting preferentially with Mo to form SrMoO4. The LSCF grain boundary was found to be rich in Cr and deficient in Co. These results suggest that potential Mo poisoning effects should be considered when developing metallic interconnects containing Mo.